2023
DOI: 10.46234/ccdcw2023.070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 Vaccination Against SARS-CoV-2 Omicron Variant Infection and Symptoms — China, December 2022–February 2023

Abstract: What is already known about this topic? A considerable percentage of the population has received both primary and booster vaccinations, which could potentially provide protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron infections and related symptoms. What is added by this report? The self-reported infection rate, as determined from an online survey, reached its peak (15.5%) between December 19 and 21, 2022, with an estimated 82.4% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 7 publications
2
17
3
Order By: Relevance
“…This result seems to be contrary to the fact that SARS-CoV-2 infection risk increases with age, but it may reflect that the elderly population is more likely to take behaviours to reduce exposure risk like mask using, avoiding close contact with persons with COVID-19, or reducing outdoor activities during the outbreak period. Besides, the results of another survey conducted in China from December 2022 to February 2023 also showed that the COVID-19 attack rate of the elderly was about 10% lower than young adults [ 18 ], which was consistent with our findings. Although the elderly reported a lower overall attack rate of COVID-19 breakthrough cases, they accounted for a higher proportion of outpatient visits and hospitalization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result seems to be contrary to the fact that SARS-CoV-2 infection risk increases with age, but it may reflect that the elderly population is more likely to take behaviours to reduce exposure risk like mask using, avoiding close contact with persons with COVID-19, or reducing outdoor activities during the outbreak period. Besides, the results of another survey conducted in China from December 2022 to February 2023 also showed that the COVID-19 attack rate of the elderly was about 10% lower than young adults [ 18 ], which was consistent with our findings. Although the elderly reported a lower overall attack rate of COVID-19 breakthrough cases, they accounted for a higher proportion of outpatient visits and hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…A nationwide outbreak of COVID-19 associated with omicron-predominate subvariants BA.5.2, BA.2.76, and BF.7 occurred in China at the end of the year 2022, causing a wave of large-scale infections among the population, despite a high ICV vaccination coverage [ 18 ]. In this study, we did a retrospective survey of a large, diverse population of people aged 18 years or older, from six provinces in China, and identified an overall breakthrough infection proportion of 62.7% among the responders.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the infection rate of COVID-19 in aPAP patients was a little bit higher than that estimated by the Chinese Center for Disease Control and Prevention (CDC) in the same period. The infection rate of COVID-19 in aPAP patients in this study was 95.12%, while the CDC estimated that the infection rate of COVID-19 in China was 82.4% as of February 7, 2023 [12]. We believe that this is likely due to the estimated results of the CDC through online survey.…”
Section: Discussionmentioning
confidence: 61%
“…In late 2022, China revised its public health control measures [8]. Subsequently, the virus quickly spread across the country and infected over 80% of the population according to an online survey [9,10]. Given the significant number of infections, there was a growing concern that new variants might emerge within China, akin to how the Delta and Omicron variants originated [11][12][13].…”
Section: Introductionmentioning
confidence: 99%